Decision support system in oil spill cases (literature review) - Pourvakhshouri, S. Zahra; Mansor, Shattri (Emerald, 2003)
Oil pollution is one of the most important issues affecting the marine coastal environments all over the world. There are a large number of organizations to propose plans for managing the problems that coastal areas face, including various methods to combat the oil spills. This project proposes to achieve a decision support system(DSS) to assist the users/managers to choose the most suitable method for combating oil spills, according to the coastal area sensitivity. In this regard and in order to build an appropriate DSS model, some relevant documents regarding oil spills and spills management strategies, GIS- based modeling, and DSS planning were reviewed, some of which are referred to here.